The clockwork orange Drosophila protein functions as both an activator and a repressor of clock gene expression. - Richier, B.; Michard-Vanhée, C.; Lamouroux, A.; Papin, C.; Rouyer, F. (Journal of Biological Rhythms, 2008)
The Drosophila clock relies on transcriptional feedback loops that generate daily oscillations of the clock gene expression at mRNA and protein levels. In the evening, the CLOCK (CLK) and CYCLE (CYC) basic helix-loop-helix (bHLH) PAS-domain transcription factors activate the expression of the period (per) and timeless (tim) genes. Posttranslational modifications delay the accumulation of PER and TIM, which inhibit CLK/CYC activity in the late night. We show here that a null mutant of the clockwork orange (cwo) gene encoding a bHLH orange-domain putative transcription factor displays long-period activity rhythms. cwo loss of function increases cwo mRNA levels but reduces mRNA peak levels of the 4 described CLK/CYC targets, inducing an almost complete loss of their cycling. In addition, the absence of CWO induces alterations of PER and CLK phosphorylation cycles. Our results indicate that, in vivo, CWO modulates clock gene expression through both repressor and activator transcriptional functions.